Răspuns :
a. cu n ≥ 4
daca n + 6 < 2n + 3 ; 6 - 3 < 2n - n ; 3 <n adevarat n≥ 4
daca 2n +3 < 3n ; 3 < 3n - 2n ; 3 < n adevarat
⇒ n + 6 < 2n + 3 < 3n
b . n ≥ 5
daca n + 11 < 2n + 6 ; 11 - 6 < 2n - n ; 5 < n
atunci n + 11 ≤ 2n + 6 ; 5 ≤ n adevarat
daca 2n + 6 < 3n + 1 ; 6 - 1 < 3n - 2n ; 5 < n
atunci 2n + 6 ≤ 3n + 1
⇒ n + 11 ≤ 2n + 6 ≤ 3n + 1
c. n ≥ 2
daca n + 2 < 2n + 1 ; 2 - 1 < 2n - n ; 1 < n deoarece n ≥ 2
n + 2 < 2n+ 1 < 2n + 3 ≤ 3n + 1
daca 2n + 3 < 3n +1 ; 3 -1 < 3n - 2n ; 2 < n adevarat daca
2n + 3 ≤ 3n + 1
d. n ≥ 3
daca n + 5 < 2n +3 ; 5 -3 < 2n - n ; 2 < n adevarat
daca 2n + 3 < 3n + 2 ; 3 -2 < 3n - 2n ; 1 < n adevarat
daca 3n + 2 < 4n + 1 ; 2 - 1 < 4n - 3n ; 1 < n adevarat
daca 4n + 1 < 5 n ; 1 < 5n - 4n ; 1 < n adevarat
⇒ n + 5 < 2n + 3 < 3n + 2 < 4n + 1 < 5n
daca n + 6 < 2n + 3 ; 6 - 3 < 2n - n ; 3 <n adevarat n≥ 4
daca 2n +3 < 3n ; 3 < 3n - 2n ; 3 < n adevarat
⇒ n + 6 < 2n + 3 < 3n
b . n ≥ 5
daca n + 11 < 2n + 6 ; 11 - 6 < 2n - n ; 5 < n
atunci n + 11 ≤ 2n + 6 ; 5 ≤ n adevarat
daca 2n + 6 < 3n + 1 ; 6 - 1 < 3n - 2n ; 5 < n
atunci 2n + 6 ≤ 3n + 1
⇒ n + 11 ≤ 2n + 6 ≤ 3n + 1
c. n ≥ 2
daca n + 2 < 2n + 1 ; 2 - 1 < 2n - n ; 1 < n deoarece n ≥ 2
n + 2 < 2n+ 1 < 2n + 3 ≤ 3n + 1
daca 2n + 3 < 3n +1 ; 3 -1 < 3n - 2n ; 2 < n adevarat daca
2n + 3 ≤ 3n + 1
d. n ≥ 3
daca n + 5 < 2n +3 ; 5 -3 < 2n - n ; 2 < n adevarat
daca 2n + 3 < 3n + 2 ; 3 -2 < 3n - 2n ; 1 < n adevarat
daca 3n + 2 < 4n + 1 ; 2 - 1 < 4n - 3n ; 1 < n adevarat
daca 4n + 1 < 5 n ; 1 < 5n - 4n ; 1 < n adevarat
⇒ n + 5 < 2n + 3 < 3n + 2 < 4n + 1 < 5n